Patients' perspectives of healthcare-associated infection: 'you don't know what impacts it will have on your life'. (August 2022) - Mitchell, B.G.; Northcote, M.; Rickett, C.; Russo, P.L.; Amin, M.; De Sousa, F.; Pearce, K.; Sim, J.; Curryer, C.
Summary: Background: Healthcare-associated infections (HAIs) are not present on admission but are contracted while a patient is undergoing hospital treatment. While the prevalence of HAIs, and their causes and treatments have been researched in various contexts to date, patients' perspectives of contracting and living with the consequences of an HAI remain under-researched. Objective: To explore patients' experiences of having an HAI. Methods: A qualitative phenomenological study that drew on data from semi-structured interviews was conducted in order to explore the lived experiences of patients who had recently contracted an HAI while in hospital. Participants were recruited from two Australian hospitals in 2019 and 2021. Telephone interviews were conducted with 10 participants by two research team members, and transcripts from these interviews were analysed qualitatively using a thematic coding process to identify the patients' perspectives of contracting an HAI. Results: The participants had a range of different HAIs. The participants described how the experience of having an HAI can be very isolating and distressing from the patient's perspective, with life-long implications. This contributes to understanding of the way in which patients are impacted emotionally and mentally as a result of contracting an HAI. Conclusion: There is a need for improved, person-centred communication about the source, treatment and prognosis of HAIs. The findings from this study indicate the importance of considering patients' voices in their own health care.